Management of Medium and Long Term Complications Following Prostate Cancer Treatment Resulting in Urinary Diversion – A Narrative Review - Hoeh, Benedikt; Müller, Stefan C.; Kluth, Luis A.; Wenzel, Mike (Frontiers in Surgery, 2021)
The purpose of this narrative review is to discuss and highlight recently published studies regarding the surgical management of patients suffering from prostate cancer treatment complications. Focus will be put on the recalcitrant and more complex cases which might lead to urinary diversion as a definite, last resort treatment. It is in the nature of every treatment, that complications will occur and be bothersome for both patients and physicians. A small percentage of patients following prostate cancer treatment (radical prostatectomy, radiation therapy or other focal therapies) will suffer side effects and thus, will experience a loss of quality of life. These side effects can persist for months and even years. Often, conservative management strategies fail resulting in recalcitrant recurrences. Prostate cancer patients with ‘end-stage bladder’, ‘devastated outlet’ or a history of multiple failed interventions, are fortunately rare, but can be highly challenging for both patients and Urologists. In a state of multiple previous surgical procedures and an immense psychological strain for the patient, urinary diversion can offer a definite, last resort surgical solution for this small group of patients. Ideally, they should be transferred to centers with experience in this field and a careful patient selection is needed. As these cases are highly complex, a multidisciplinary approach is often necessary in order to guarantee an improvement of quality of life.